Investigation of the current collapse behaviour in GaN power HEMTs with highly adjustable pulse and measurement concept. (November 2020) - Goller, M.; Thim, M.A.; Song, J.; Kowalsky, J.; Franke, J.; Lutz, J.
Abstract: The dynamic RDSon or current collapse of Gallium Nitride (GaN) power HEMT devices was investigated under soft switching operation using a pulse test circuit, based on a half bridge configuration. The presented test and measurement setup allows device operation under adjustable high voltage and current with inexpensive measurement methods. A flexible adaption of the pulse pattern allows operation with and without biasing the device under test with high voltage before the pulse. Hence, the static and dynamic values of the R DSon can be determined in one single test setup under identical conditions and device configuration. Doing so, different stress conditions could be realized including variable drain-source blocking voltage V DS, off for adjustable stress time t stress and temperature ϑ. The results show strong dependency of R DSon on the stress time and the drain-source voltage. Furthermore, indications of a strong influence of the trapping process on dynamic effects as well as an optimal operation for the devices at very low off-state stress times in application are observed. Highlights: Gallium Nitride GaN power HEMT Dynamic RDSon Current collapse Soft switching operation